The effect of geometric dimensions on the lateral bearing capacity of the masonry arches. (November 2022) - Mahmoudi, Pedram; Asadi, Payam; Eftekhar, Mohammad Reza
Abstract: The roofs of historic structures and old buildings are frequently covered using 5&7 brick arches. Since the design of these arches is usually done against gravity loads, they will probably be vulnerable to lateral loads. The estimation of the lateral bearing capacity of 5&7 brick arches is the main goal of this study, along with investigating the effect of geometric dimension parameters on the lateral bearing capacity of these arches. The models of the examined arches are in accordance with 5&7 arches of the low slope and steep slope types. The spans studied in this research are equal to 2.5, 4.5, 6.5, and 9.5 m, and the results have been tested for a case study, the main porch of Gonabad Grand Mosque in Iran. The specifications of the building materials used in this research were determined using laboratory studies, and all analyses were performed by ANSYS software. Evaluating the ratio of lateral load-carrying capacity to the weight of the structure for different arches showed that the optimal ratio of the thickness of the pier to the spans for low slope and steep slope 5&7 arches was about 0.24.